2021
DOI: 10.3389/fgeed.2021.784233
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Knockout of Eukaryotic Translation Initiation Factor 4E Confers Bymovirus Resistance in Winter Barley

Abstract: The Eukaryotic Translation Initiation Factor 4E (EIF4E) is a well-known susceptibility factor for potyvirus infections in many plant species. The barley yellow mosaic virus disease, caused by the bymoviruses Barley yellow mosaic virus (BaYMV) and Barley mild mosaic virus (BaMMV), can lead to yield losses of up to 50% in winter barley. In autumn, the roots of young barley plants are infected by the soil-borne plasmodiophoraceous parasite Polymyxa graminis L. that serves as viral vector. Upon viral establishment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…The proportion of mutants among primary transgenic plants was 0%-57%, which is on par with previously published results in targeted mutagenesis with cas9 in barley (see Koeppel et al (2019), Table 1). The comparatively high proportion of homozygous mutants in M 1 using the cultivar 'Igri' indicated that cas9 and gRNA could induce mutations prior to spontaneous genome duplication, which is a frequent occurrence during (haploid) microspore-derived plant regeneration (see also Hoffie et al (2021)). However, for the same reason, T-DNA-free individuals occurred rather rarely among Cas endonucleaseinduced mutants with an 'Igri' background.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The proportion of mutants among primary transgenic plants was 0%-57%, which is on par with previously published results in targeted mutagenesis with cas9 in barley (see Koeppel et al (2019), Table 1). The comparatively high proportion of homozygous mutants in M 1 using the cultivar 'Igri' indicated that cas9 and gRNA could induce mutations prior to spontaneous genome duplication, which is a frequent occurrence during (haploid) microspore-derived plant regeneration (see also Hoffie et al (2021)). However, for the same reason, T-DNA-free individuals occurred rather rarely among Cas endonucleaseinduced mutants with an 'Igri' background.…”
Section: Discussionmentioning
confidence: 99%
“…Since only EIF4E ‐mediated resistance is present in current winter barley cultivars, there is an urgent need for new resistance mechanisms in winter barley breeding material. The full knockout of HvEIF4E renders barley resistant to bymovirus infection, as described for other plants, but it is associated with a substantial yield penalty (Hoffie et al ., 2021 ). In the landrace HOR1363 (formerly PI1963) and the Russian cultivar ‘Russia 57’, rym11 , a locus associated with resistance to all known strains of BaYMV and BaMMV, was described (Nissan‐Azzouz et al ., 2005 ; Sedláček and Mařík, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Considering all the evidence, it seems that the gene HORVU.MOREX.r3.6HG0573610 is the most likely candidate for BaMMV resistance encoded by rym15 . Functional analysis of the two candidate genes, for example by gene editing ( Hoffie et al, 2021 ) will likely lead to cloning of the causal gene for rym15 .…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, editing of other S genes can impair plant growth and lead to developmental defects. For example, knockout variants of the barley host factor gene eIF4E ( Eukaryotic Translation Initiation Factor 4E ) show decreased total grain yield per plant ( Hoffie et al., 2021 ). The loss of function of eIF4E or its isoforms eIF(iso)4E leads to dwarfism or the loss of fertility in Arabidopsis, tobacco, tomato, and melon ( Combe et al., 2005 ; Mazier et al., 2011 ; Callot and Gallois, 2014 ; Patrick et al., 2014 ; Gauffier et al., 2016 ; Pechar et al., 2022 ).…”
Section: Discussionmentioning
confidence: 99%